Relationship between knowledge, attitudes, and practices and COVID-19 vaccine hesitancy: A cross-sectional study in Taizhou, China - Lin, Xiao-Qing; Zhang, Mei-Xian; Chen, Yan; Xue, Ji-Ji; Chen, He-Dan; Tung, Tao-Hsin; Zhu, Jian-Sheng (Frontiers in Medicine, 2022)
Objective This study aimed to explore COVID-19 vaccine hesitancy in Chinese adults and analyzed the relationship between knowledge, attitudes, practices (KAP), and COVID-19 vaccine hesitancy. Methods A population-based self-administered online survey was conducted in Taizhou, China to evaluate the population's hesitancy to receive COVID-19 vaccination. A total of 2.463 adults received the invitation for the survey through WeChat (A Chinese app that is used for chat, social media, and mobile payment), and 1.788 interviewees answered the structured questionnaire. The overall response rate was 72.6%. Results Total 45.2% of people were hesitant about the COVID-19 vaccination. Using binary logistic regression analysis, we found low perception of safety (Model 3: Odds ratio = 2.977, Confidence interval: 2.237–3.963) and efficacy (Model 3: OR = 1.904, 95%CI: 1.462–2.479) of the COVID-19 vaccine in adults is the most important risk factor for COVID-19 vaccine hesitation. People who know more about COVID-19 vaccination are less hesitant (Model 2: OR = 0.967, 95% CI: 0.951–0.983). People who did not seek information independently about the COVID-19 vaccine are more likely to be skeptical (Model 4: OR = 1.300, 95% CI: 1.058–1.598, P = 0.013). Conclusion In China, the population had higher levels of COVID-19 vaccine hesitation, and their knowledge of the COVID-19 vaccine, perceptions of safety and efficacy, and physical health status were significantly associated with vaccine hesitation. These results provide ideas for promoting COVID-19 vaccination and intervention and have far-reaching implications for further strengthening research on vaccine hesitancy in COVID-19 and exploring strategies for COVID-19 vaccine promotion.